2013
DOI: 10.2139/ssrn.2266538
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Women Farm Operators and Their Farms

Abstract: The U.S. Department of Agriculture (USDA) prohibits discrimination in all its programs and activities on the basis of race, color, national origin, age, disability, and, where applicable, sex, marital status, familial status, parental status, religion, sexual orientation, genetic information, political beliefs, reprisal, or because all or a part of an individual's income is derived from any public assistance program. (Not all prohibited bases apply to all programs.) Persons with disabilities who require altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 7 publications
(2 reference statements)
6
67
0
Order By: Relevance
“…Its results are briefly discussed below. As mentioned above, a 2013 report by the successor to the Bureau of Agricultural Economics, the USDA Economic Research Service, also included data on the number of zero-sales farms by gender in the 1982 and 2007 censuses (Hoppe & Korb, 2013).…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Its results are briefly discussed below. As mentioned above, a 2013 report by the successor to the Bureau of Agricultural Economics, the USDA Economic Research Service, also included data on the number of zero-sales farms by gender in the 1982 and 2007 censuses (Hoppe & Korb, 2013).…”
Section: Data Sourcesmentioning
confidence: 99%
“…While Gilbert, Sharp, and Felin limited their discussion to black farmers, the same "false 'trend'" appears to exist for other groups disproportionately likely to operate small-scale farms. A 2013 USDA report on women farmers compared COA data from 1982 and 2007 and found that zero-sales farms had increased fivefold-almost twice as fast as any other sales class during that period (Hoppe & Korb, 2013). The authors also found that almost 60 percent of the increase in women farmers between 1982 and 2007 was due to the growth of zero-sales farms (Hoppe & Korb, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent with these shifts in the structure of agriculture is a demographic shift in who is farming. Women in particular are an increasing proportion of farmers (Hoppe and Korb ). In 1978, women were 5 percent of principal operators compared with 14 percent in 2007 (Hoppe and Korb ).…”
Section: Introductionmentioning
confidence: 99%
“…Women in particular are an increasing proportion of farmers (Hoppe and Korb ). In 1978, women were 5 percent of principal operators compared with 14 percent in 2007 (Hoppe and Korb ). When multiple operators were counted on farms, women constituted 30 percent of all farm operators in 2007, which represented a 29 percent growth in the number of women farm operators in the United States between 2002 and 2007 (Hoppe and Korb ; USDA ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation